2011
DOI: 10.3389/fpsyg.2011.00258
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Oxytocin Administration on Charitable Donating is Moderated by Experiences of Parental Love-Withdrawal

Abstract: Oxytocin has been implicated in a variety of prosocial processes but most of this work has used laboratory tasks (such as the ultimatum game or the dictator game) to evaluate oxytocin’s prosocial effects. In a double blind randomized trial we examined the influence of intranasal administration of oxytocin on real, high-cost donating money to a charity without any expectation for reciprocation. Participants in the current study were 57 female undergraduate students, aged 18–30 years, who received a nasal spray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 48 publications
(90 reference statements)
4
53
0
1
Order By: Relevance
“…In several studies, oxytocin was shown to facilitate prosocial behavior including increased charity donations (van Ijzendoorn et al, 2011). Recently, MDMA was shown to have empathy-enhancingand prosocial effects, which were paralleled by an increase of oxytocin plasma levels .…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, oxytocin was shown to facilitate prosocial behavior including increased charity donations (van Ijzendoorn et al, 2011). Recently, MDMA was shown to have empathy-enhancingand prosocial effects, which were paralleled by an increase of oxytocin plasma levels .…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, oxytocin was shown to facilitate prosocial behavior including increased charity donations (van Ijzendoorn et al, 2011). Recently, MDMA was shown to have empathy-enhancing and prosocial effects, which were paralleled by an increase of oxytocin plasma levels .…”
Section: Discussionmentioning
confidence: 99%
“…The context-dependent nature of the effects of OT is well demonstrated in a series of studies conducted on trust, in which exogenous administrations of OT increased participants’ trust of individuals perceived as part of the in-group, but increased non-cooperation toward out-group members who were perceived as potential threats (De Dreu et al, 2010; De Dreu et al, 2012). The person-dependent nature of the effects of OT is well captured in a growing number of studies that demonstrate null effects of exogenous OT in individuals with adverse early caregiving experiences, whether assessed by reported severity of childhood abuse, neglect, or loss (Meinlschmidt and Heim, 2007), memories of parental love-withdrawal (Riem et al, 2013; van Ijzendoorn et al, 2011), or recollections of harsh parenting experiences (Bakermans-Kranenburg et al, 2012). Considering that the development of one’s OT system is critically modified by the quality of early caregiving one receives (Champagne, 2008; Meaney, 2001), it is possible that the OT system may have been altered at a more fundamental level, possibly at the level of receptors, in individuals with early adverse experiences.…”
Section: Oxytocin: a Novel Therapeutic For Postpartum Depression?mentioning
confidence: 99%